Failure Mode Analysis of Injection Molding Machines Using FMEA to Improve Production Reliability - Bayu Wahyudi; Asrul Fole; Muhamad Alfi Syahrin; Nurul Binti Gafar; Yasmin (Journal of Industrial System Engineering and Management, 2026)
Production reliability plays an important role in maintaining operational efficiency and product quality in manufacturing industries, particularly in injection molding machine systems. However, machine failures often cause downtime, defective products, and increased maintenance costs. This study aims to analyze failure modes in injection molding machines using the Failure Mode and Effects Analysis (FMEA) method to improve production reliability at the South Sumatra Palm Oil Processing Industry. The research employed a quantitative descriptive-analytical approach, using observations, interviews, documentation, and maintenance records collected during August 2025. The analysis focused on critical machine components, including the mold, heater band, cutting system, hydraulic pump, and thermocouple. The results showed that the mold failure coded M1 had the highest Risk Priority Number (RPN) of 140, followed by the cutting failure C1 with 120 and the mold closing failure M2 with 108. Pareto analysis indicated that approximately 60% of operational disruptions were caused by four dominant failures. The proposed preventive maintenance and inspection strategies are expected to significantly reduce operational disruptions and improve production reliability.